2014
DOI: 10.1155/2014/620530
|View full text |Cite
|
Sign up to set email alerts
|

Binding Sites of miR-1273 Family on the mRNA of Target Genes

Abstract: This study examined binding sites of 2,578 miRNAs in the mRNAs of 12,175 human genes using the MirTarget program. It found that the miRNAs of miR-1273 family have between 33 and 1,074 mRNA target genes, with a free hybridization energy of 90% or more of its maximum value. The miR-1273 family consists of miR-1273a, miR-1273c, miR-1273d, miR-1273e, miR-1273f, miR-1273g-3p, miR-1273g-5p, miR-1273h-3p, and miR-1273h-5p. Unique miRNAs (miR-1273e, miR-1273f, and miR-1273g-3p) have more than 400 target genes. We esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…Location of binding site in the protein coding region facilitates its conservation in evolution, especially, if the corresponding oligopeptide plays an important role in the function of protein. Similar results were obtained earlier [26,27].…”
Section: Rssgrrggss----rheksx Pabsupporting
confidence: 92%
“…Location of binding site in the protein coding region facilitates its conservation in evolution, especially, if the corresponding oligopeptide plays an important role in the function of protein. Similar results were obtained earlier [26,27].…”
Section: Rssgrrggss----rheksx Pabsupporting
confidence: 92%
“…The up-regulation of miR-1273g-3p and its involvement in promoting cell migration, proliferation, and invasion via CNR1 gene have also been described in both lung and colorectal cancer cell lines (35,36). Furthermore, several binding sites for miR-1273g-3p have been identified on mRNAs of several other genes (NOL9, PLCXD1, ZNF490, CYP20A1, GNL3L, PPM1K, RBMS2, SAR1B, SLC35E2, IRCQ, ZNF850, MDM4) by using the target gene prediction program (37).…”
Section: Discussionmentioning
confidence: 91%
“…miR‐1273g‐3p, a member of the miR‐1273 family, is a newly discovered miRNA in 2011 . Hou's study showed that miR‐1273g‐3p could promote the migration of lung cancer A549 cells by inhibiting the expression of the cannabinoid receptor type 1 (CNR1) .…”
Section: Discussionmentioning
confidence: 99%